1990
DOI: 10.1101/gad.4.1.75
|View full text |Cite
|
Sign up to set email alerts
|

The block to transcription elongation is promoter dependent in normal and Burkitt's lymphoma c-myc alleles.

Abstract: Aberrant c-myc expression patterns occur in human Burkitt's lymphoma cells, which consistently exhibit c-myc chromosomal translocations, mutations within and flanking the translocated allele, a loss of the block to transcription elongation in exon 1, and a promoter shift to use of the upstream P1 promoter. To define the mechanism responsible for the loss of transcription elongation blockage and resulting c-myc deregulation in Burkitt's lymphoma, we analyzed transcription patterns after transfer of normal and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
2
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 45 publications
5
74
2
1
Order By: Relevance
“…There is no obvious correlation between the single nucleotide mutations detected in the c-MYC exon 1 and the major polymerase II pausing/ termination site described in this exon. Thus, the data do not lend any strong support to a connection between transcriptional pausing and antibody hypermutation although (I) the pause sites in the translocated c-MYC could di er from those in the germline allele (Spencer et al, 1990) and (II) two of the three insertion/duplication events that we observed in the Ramos c-MYC are within the homopolymeric dT stretch that constitutes the major exon 1 pause site.…”
Section: Discussioncontrasting
confidence: 63%
“…There is no obvious correlation between the single nucleotide mutations detected in the c-MYC exon 1 and the major polymerase II pausing/ termination site described in this exon. Thus, the data do not lend any strong support to a connection between transcriptional pausing and antibody hypermutation although (I) the pause sites in the translocated c-MYC could di er from those in the germline allele (Spencer et al, 1990) and (II) two of the three insertion/duplication events that we observed in the Ramos c-MYC are within the homopolymeric dT stretch that constitutes the major exon 1 pause site.…”
Section: Discussioncontrasting
confidence: 63%
“…The human c-myc gene is regulated by a block to transcription elongation during a number of in vivo processes such as differentiation of HL-60 cells and stimulation of quiescent cells by mitogens (2,29). In addition, the block to transcription elongation is lost in several tumor cells, such as HeLa and Burkitt's lymphoma cells, contributing to high or constitutive levels of c-myc mRNA in these cells (52,54).…”
mentioning
confidence: 99%
“…This assay has been used to study transcription arrest from the human c-myc gene (3,33,54), the murine c-myc gene (45,59), the human and mouse adenosine deaminase genes (8,9,40), and the Xenopus oa-tubulin gene (34).…”
mentioning
confidence: 99%
“…9 The exon 1 mutation prevents the Pol II block and leads to constitutive Pol II read-through and elevated MYC. 8,[10][11][12] The complexity of the MYC promoter and regulation by post-initiation release of paused Pol II reflects the multitude of signaling inputs converging on MYC transcription. As early studies found a correlation between MYC promoter sensitivity to nuclease cleavage and expression levels, 9,10,13 analysis of nucleasesensitive elements was used as a means to understand integration of signaling inputs.…”
Section: Fuse-a Nuclease-sensitive Site In the Myc Promoter Modulatesmentioning
confidence: 99%